The Consecutive Interpreting Process Done by Students of English Education Department of IKIP Saraswati in Academic Year 2017/2018 - Ni Putu Meri Dewi Pendit (WACANA : MAJALAH ILMIAH TENTANG BAHASA, SASTRA DAN PEMBELAJARANNYA, 2019)
Translation and Interpretation is one of the subject taught in English Education Department of IKIP Saraswati. Students were taught to be able to do both translating and interpreting. They were practicing them on the sixth semester. Observation was conducted during the practice of consecutive interpreting. It is an activity which involves the interpreter converting the words of the first language into the other, directly after the first language is spoken. This paper discuses the strength and the weaknesses of consecutive interpreting conducted by the students of English Education Department.